Felling Ficus: The Cultural Status of Fig Trees in a Rural Assamese Community, India - Cottee-Jones, H Eden W; Whittaker, Robert J. (Ethnobiology Letters, 2015)
Scattered fig (Ficus spp. Moraceae) trees are critically important for biodiversity conservation in tropical rural landscapes. By providing large fruit crops, they help maintain seed dispersal networks and facilitate forest restoration. The conservation of fig trees scattered across rural landscapes is therefore vital for the preservation of ecosystem services and biodiversity beyond the borders of protected areas. Given the threats to scattered fig trees, it is increasingly important to identify potentially effective local conservation strategies that accommodate existing perceptions of their value. We used ethnographic techniques to assess the attitudes of villagers towards fig trees in the village of Komargoan and its surroundings in Assam, India. As reported for other parts of South Asia, we found fig trees have significant sacred status, which included taboos against cutting them down. However, we discovered mixed and sometimes contradictory understandings of the religious attributes of fig trees, which were sometimes believed to be inhabited by gods or ancestral spirits. The benefits most commonly associated with fig trees by interviewees were their aesthetic beauty, large size, and shade during the daytime heat. When the presence of these trees incurred economic costs, their religious, aesthetic, and practical benefits were not sufficient reasons to prevent people from cutting them down, although often saplings would be planted in another place as compensation. Unexpectedly, figs were only planted by respected members of the community, usually older men, who had sufficient social status. Any conservation strategy aiming to sustain the abundance of figs in rural Assam is more likely to be successful if these cultural views are taken into account.